A Rare Cause of Proteinuria: Sarcoidosis with Isolated Kidney and Muscle Involvement - Yelda DELİGÖZ BİLDACI; Filiz YILDIRIM; Özcan UZUN; Serpil Muge DEĞER; Sülen SARIOĞLU; Caner ÇAVDAR (Forbes Tıp Dergisi, 2023)
Sarcoidosis is a multisystemic disease with non-caseating granulomas presenting with lymphadenomegaly, lung involvement, eye disorders, and/or skin involvement. Kidney and muscle involvement alone is rare in sarcoidosis. Our article presents a case diagnosed with isolated kidney and muscle involvement without lung involvement. Patient with no known history of hypertension or diabetes mellitus, granuloma was detected in the kidney biopsy performed due to elevated creatinine and 24-hour urine proteinuria levels with accompanying hypercalcemia. Due to the patient's severe muscle pain, the biopsy was also found to be compatible with granuloma. In the thorax and abdomen imaging of the patient with elevated angiotensin converting enzyme, no significant pathology was detected, including an infectious etiology. The patient was diagnosed with extrapulmonary sarcoidosis, and methylprednisolone treatment was started. Patients' symptoms, as well as laboratory parameters, regressed following the aforementioned treatment. Although sarcoidosis presents primarily with pulmonary involvement, it may rarely present with extrapulmonary findings. At this point, tissue biopsies can lead an important way to correct diagnosis.